The People Vs Tech : How the Internet is Killing Democracy and How we Save it - Bartlett, Jamie (London Eburry Press, 2018)
And, in light of recent data breach scandals around companies like Facebook and Cambridge Analytica, what does that mean for democracy, our delicately balanced system of government that was created long before big data, total information and artificial intelligence?
Include Acknowledgment
Keywords: Subculture -- Internet--Moral and ethical aspects